The presence of confirmation bias in the recycling habits of individuals in Indonesia resulted in the occurrence of motivated reasoning - Wiradimadja, Dafi Dinansyah; Mori, Hisatsuna (Technium Social Sciences Journal, 2023)
The complexity of Indonesia’s waste problem can be attributed to the lack of awareness among the general public regarding the potential repercussions of garbage. Another element that contributes to the issue is the increasing standard of living within the community. However, there is a lack of agreement on waste management practises and a lack of community engagement in maintaining cleanliness and effective trash disposal. The data utilized in this study were collected by several methods, including direct observation, semi-structured interviews, review of secondary material, and a combination of qualitative and quantitative approaches. There are numerous factors that contribute to the unreasonable behaviour exhibited by respondents. The decision-making process and behavioural patterns of individuals are significantly influenced by various internal elements, particularly those of a psychological nature. The research showed that highly significant number of respondents have adequate knowledge regarding waste separation and the notion of what they should do for environmentally sound village, but 64% still burn their garbage and 76% not separating it. Various individual variables and psychological situations, such as confirmation bias, might contribute to environmentally unfriendly behaviour, despite individuals possessing adequate knowledge. Even the presence of appropriate trash disposal options may have limited impact on altering their behaviour. The subsequent topic of discussion pertains to the presence of biassed behaviour, which can significantly influence individuals’ decision-making processes, particularly in relation to activities such as burning waste. While individuals may possess a cognitive awareness and express their thoughts explicitly in this regard, it is often the case that their motivations unconsciously shape their judgements, often without their own realisation. For instance, individuals who refute the degradation of their surroundings sometimes remain unaware of how their inclination towards maintaining a clean home or backyard bias their evaluation of the available in-formation they already gain. Based on the findings of the research, it can be observed that a significant proportion of individuals residing in Bendungan Village engage in the practise of waste disposal.